Faktor Penentu Pertumbuhan Ekonomi Indonesia - Susanti, Rina; Silvia, Engla Desnim; Ariani, Fatma (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to determine: the effect of inflation on Indonesia's economic growth, the effect of HDI on Indonesia's economic growth and the effect of unemployment on economic growth in Indonesia. The data used in this research is secondary data sourced from the websites of various agencies including BPS, aseanstats.org, and kidb.adb.org, from 1993-2022. This research uses the Autoregressive Distributed Lag or ARDL analysis tool model. The ARDL model is a combination of autoregressive (AR) and distributed lag (DL) methods. The AR method is a method that uses one or more past data from the dependent variable, while DL is a regression method that involves data at the present and past times from the independent variable. This model can differentiate short-term and long-term responses of the variables studied. The findings of this study indicate that there is cointegration between the variables used in this study so that the ARDL test can be carried out. The results of short-term data processing show that inflation has had a negative and significant effect on Indonesia's economic growth in the current year, two and three years previously. Meanwhile, HDI has a significant influence in the current year and the previous two years. Meanwhile, unemployment has had a significant negative influence in the current year on Indonesia's economic growth. In long-term estimates, inflation and unemployment have a negative and significant effect on economic growth, however, HDI does not have a significant effect on Indonesia's economic growth.